2012
DOI: 10.7150/thno.3722
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Iodide Symporter for Nuclear Molecular Imaging and Gene Therapy: From Bedside to Bench and Back

Abstract: Molecular imaging, defined as the visual representation, characterization and quantification of biological processes at the cellular and subcellular levels within intact living organisms, can be obtained by various imaging technologies, including nuclear imaging methods. Imaging of normal thyroid tissue and differentiated thyroid cancer, and treatment of thyroid cancer with radioiodine rely on the expression of the sodium iodide symporter (NIS) in these cells. NIS is an intrinsic membrane protein with 13 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
89
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 55 publications
0
89
0
Order By: Relevance
“…This is due to its ability to increase the rate of patient survival compared to patients who do not receive I-131 [3,4]. This therapy is based on the uptake of radioiodine into cancer cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to its ability to increase the rate of patient survival compared to patients who do not receive I-131 [3,4]. This therapy is based on the uptake of radioiodine into cancer cells.…”
mentioning
confidence: 99%
“…This therapy is based on the uptake of radioiodine into cancer cells. In thyroid cancer, the uptake of I-131 is affected by the natrium/iodide symporter (NIS) expression [3,5,6]. A natrium/iodide symporter brings two sodium ions (Na + ) and one iodide ion (I -) to cross the membrane against its ionic concentration gradient [3,6,7].…”
mentioning
confidence: 99%
“…It has been known that non thyroidal tissues also express NIS however only small part of these NIS expressing tumors do show iodine uptake [20]. The NIS expression in other tissues than thyroid tissue like salivary glands, gastric mucosa and mammary gland are lower than thyroid tissue [21]. Additionally it has been observed that malign breast tissue as well as benign breast tissue may retain iodine and thus the first applications cover breast cancer with NIS transfection [9].…”
Section: Other Methods In Dedifferentiationmentioning
confidence: 99%
“…Molecular imaging is defined as the visual representation, characterization, and quantification of biological processes at the cellular and subcellular levels within intact living organisms; this can be achieved by various imaging technologies such as nuclear imaging, optical imaging, magnetic resonance imaging (MRI), ultrasound imaging, and computed tomography (CT) [1]. Although these modalities are actively used for sensing molecular and cellular processes in preclinical studies, the majority of imaging techniques remain unapplied in the clinical field due to various unresolved issues, such as safety, poor tissue penetration of the imaging signal, and limited sensitivity.…”
mentioning
confidence: 99%
“…Although these modalities are actively used for sensing molecular and cellular processes in preclinical studies, the majority of imaging techniques remain unapplied in the clinical field due to various unresolved issues, such as safety, poor tissue penetration of the imaging signal, and limited sensitivity. So far, nuclear or fusion imaging modalities with the nuclear medicine component are the actively used molecular imaging modalities in the clinical field [1][2][3].…”
mentioning
confidence: 99%